Republic of Kazakhstan Tax Strategy Paper : Volume 1. A Strategic Plan for Increasing the Neutrality of the Tax System in Non-Extractive Sectors - World Bank (Washington, DC, 2014)
This study focuses on the tax system for non-subsurface users in Kazakhstan. It takes as given the tax reform package that the authorities and stakeholders are designing, but proposes a number of additional steps to be taken over the next 2-3 years aimed at maximizing the benefits of tax neutrality on competitiveness. The first volume of this report mainly focuses on tax policy: taxes on labor, capital, and consumption. A draft report on administration was also produced for discussion, which includes an initial assessment for organization, planning and staffing, a large taxpayers unit, anti-corruption issues, taxpayer services and education, audit and inspections, collection activities, and legal issues and appeal. The second volume of the tax strategy paper examines tax administration issues, and identifies functional areas that require attention in the short, medium and longer-term. This examination represents an initial diagnostic and is not a final blueprint for modernization. The nine areas diagnosed are: organizational structure, human resource and training; anti-corruption; taxpayer service and education; large taxpayers; audit/inspection; collection; information technology; and legal and appeals.